2015
DOI: 10.1142/s0218625x15500353
|View full text |Cite
|
Sign up to set email alerts
|

WETTING BEHAVIOR IN ULTRASONIC VIBRATION-ASSISTED BRAZING OF ALUMINUM TO GRAPHITE USING Sn-Ag-Ti ACTIVE SOLDER

Abstract: In this study, Sn-Ag-Ti ternary alloy has been used as the active solder to braze pure aluminum and graphite in atmospheric conditions using ultrasonic vibration as an aid. The authors studied the formation, composition and decomposition temperature of the surface oxides of the active solder under atmospheric conditions. In addition, the wettability of Sn-5Ag-8Ti active solder on the surface of pure aluminum and graphite has also been studied. The results showed that the major components presented in the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The surface of a steel sample working with a moist ring shows a decrease in roughness after 15 min. At this stage of research the theory already confirms that the presence of water affects the lubricating properties of these materials [11,14,15].…”
Section: Surface Roughnessmentioning
confidence: 93%
See 1 more Smart Citation
“…The surface of a steel sample working with a moist ring shows a decrease in roughness after 15 min. At this stage of research the theory already confirms that the presence of water affects the lubricating properties of these materials [11,14,15].…”
Section: Surface Roughnessmentioning
confidence: 93%
“…According to one theory [7] graphite shows good lubricating properties due to water adsorption. The adsorbed water molecules on the main sliding planes reduce the adhesion between them and thus reduce the coefficient of friction as they slide [11,14,15]. The problem turns out to be that too much water washes away the resulting graphite wear particles, which are necessary for the formation of the sliding layer [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another investigated aspect of the Sn-Ag-Ti-based solder was its spreadability on porous graphite when applying ultrasonic vibrations. The authors' results [10,11] have shown that the application of ultrasonic waves during soldering allows the active solder to spread on the surface of the graphite at a relatively low temperature under atmospheric conditions. The oxide layer on the molten solder forms a compact layer of a certain thickness which prevents the liquid solder from wetting the base material.…”
Section: Soldering With Active Soldersmentioning
confidence: 99%
“…The effect of ultrasound on bond formation between the solder alloyed with Ti and a semiconductor or ceramic substrate is documented in several professional publications [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%